MENINGKATKAN KEMAMPUAN MEMBACA PADA MATA PELAJARAN BAHASA INDONESIA DENGAN MENGGUNAKAN MEDIA BIGBOOK PADA PESETA DIDIK KELAS II SDN 04 KLEGEN - Retno Wati; Purwandari; Setyaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to determine the effect of using big book media to improve reading skills in class II students at SDN 04 Klegen. Classroom Action Research (PTK) is a type of research used to solve learning problems with the aim of improving the quality of learning in the classroom. This research was carried out in two cycles, each cycle consisting of four stages, namely planning, action, observation and reflection. Classroom action research was carried out in class II of SDN 04 Klegen with a total of 13 students. In order to achieve the objectives of this research, researchers used big book media. Data on the influence of using bigbook media to improve students' reading skills were collected using performance tests and observation methods. The results obtained during this research in cycle I were 53.84% and increased in cycle II by 84.61%. The increase in students' reading ability from cycle I to cycle II was 30.77%. It can be concluded that the use of big book media has an effect on increasing the reading skills of class II students at SDN 04 Klegen.